Building a free and responsible press throughout the Commonwealth - Lord Black of Brentwood (2012)
Highlights the issue of freedom of expression emanating from the report on Commonwealth media law by the CPU Media Trust which identifies the continued use of legislation and other measures to restrict the freedom of expression in the media, and recommends steps for governments to take to protect and enhance this fundamental right..